USE OF BENDASE IN THE TREATMENT OF STRONGYLATOSIS OF GOATS - Rakhimberganov. B. Sh.Rakhimberganov. B. Sh.; Taylakov T.I. (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the prevalence and prevention of various gastrointestinal strongylatosis among goats in Samarkand region, countermeasures have been studied.